Aproximações entre a história da leitura e da alfabetização - Sena, Fabiana; Kulesza, Wojciech Andrzej (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
The discussions in recent decades having as object the history of reading highlighted the autonomy of the individual reader in the interpretation of written texts. In this context we emphasize that Paulo Freire and Roger Chartier give to the reader his own meanings to texts, tuning it with their lived, known experiences and previous readings. In this perspective, we seek to approximate the cultural history and Paulo Freire propositions about reading and writing because we understand that his literacy practices, especially from their original formulations, accentuated the importance of taking into account the prior knowledge of the students. To be literate, to grasp the world through words, it is inextricably linked with the process of knowledge of the words that are meaningful to the learner and how he uses them to represent the world in which he lives. In this paper are drawn lines of convergence between these two approaches to reading/writing practices, showing their similarities, and pointing out the fruitfulness of this analytical perspective.